Does supplementing β-mannanase modulate the feed-induced immune response and gastrointestinal ecology in poultry and pigs? An appraisal - Kiarie, Elijah G.; Steelman, Samantha; Martinez, Marco (Frontiers in Animal Science, 2022)
The provision of adequate and balanced nutrients is critical for efficient and profitable animal protein production. However, non-nutritive components in feedstuffs can elicit responses that can negatively impact nutrient utilization efficiency. For example, dietary β-mannans are recognizable by cell surface mannose receptors are pivotal for diverse cellular functions. This review will evaluate the physiological implications of dietary native β-mannans, the utility of supplemental feed β-mannanase in hydrolyzing β-mannans, and subsequent metabolic responses. Dietary native β-mannans have been implicated in inadvertent stimulation of immune response through a phenomenon called the feed-induced immune response (FIIR), that has been associated with intestinal inflammation and depression in animal performance. Supplemental β-mannanase blunted the FIIR by hydrolyzing native β-mannans to smaller fragments with a reduced ability to stimulate the innate immune system as indicated by the modulation of oxidative stress, mucosal permeability, and blood concentration of acute phase proteins and immunoglobulins in broilers and piglet models. Moreover, β-mannanase hydrolysis of native β-mannans to mannooligosaccharides (MOS) impacted gastrointestinal microbial ecology. Indeed, β-mannanase-derived MOS reduced the concentration of pathogenic bacteria such as Escherichia coli and Salmonella and increased the production of short-chain fatty acids in gastrointestinal tracts of various animal models. Consequently, by hydrolyzing native β-mannans, supplemental β-mannanase may have nutritional, metabolic, and microbial ecology benefits. In summary, integrating multi-functional feed additives such as β-mannanase into feeding programs for monogastric animals will be critical for efficient and sustainable animal protein production in the context of evolving challenges such as the mandated elimination of use of antibiotics for growth promotion.